ANALISYSIS OF FINANCIAL STATEMENTS TO ASSESS FINANCIAL PERFORMANCE AT PT. ASTRA INTERNATIONAL TBK PERIOD 2018-2022 - Yeni Prastika; Mufidatul Himmah (SEAN Institute, 2023)
The reason the researchers chose PT Astra Internasional Tbk, as the object of research is due to the company's unstable financial condition in generating profits. One of the tools to assess financial performance can be done using financial ratios. The purpose of this study was to determine how the financial performance of PT Astra International Tbk using the analysis of liquidity ratios, solvency ratios, profitability ratios and activity ratios. The type of research used is descriptive quantitative using secondary data sources obtained from the financial statements of PT Astra International Tbk for the period 2018-2022 as well as additional data such as documents and others. Technical data analysis in this study using financial ratio analysis. The results showed that the average result of the liquidity ratio using the current ratio indicator was 1.40%, the quick ratio was 117.4%, and the cash ratio was 42.90%, this shows that the company's performance based on the liquidity ratio is still considered unfavorable because it is still below the industry standard, this means that the company is not good enough to pay its short term. Based on the average results of the solvency ratio using the debt to asset ratio indicator of 44.18% and the debt to equity ratio of 79.82%, this shows that the company's performance based on the solvency ratio is considered quite good because it meets industry standards and the company is good enough to pay overall debt with its capital and assets. Based on the average results of the profitability ratio using the return on assets indicator of 77.55%, return on equity of 13.58%, net profit margin of 11.53%, and gross profit margin of 21.91%, this shows that the company's performance is not good enough in making a profit because the company is not optimal in utilizing its assets. Based on the average results of the activity ratio using the inventory turnover indicator of 7.58% and asset turnover of 65%, it shows that the company's performance is considered poor because it is carried by industry standards, this means that the company has not been efficient in managing its assets.